2014
DOI: 10.2533/chimia.2014.505
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Switches as Platforms for Information Processing

Abstract: This article shows how to teach molecules the basics of logic and how to integrate complicated logic operations with relatively simple molecules. A special focus is put on the realization of multi-level fluorescent switches with chemical inputs as well as on the demonstration of various memory-based operations with alloptical photochromic switches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In the case of simple organic,o rc oordination compounds, [3] potential "outputs"c an be ac haracteristicc hange in both the absorption or the emission spectra of ac ompound. [4] These have been demonstrated elegantly by de Silva, [5] Andreasson, [6] and Pischel [7] amongsto thers. [8] Through our own work, we have demonstrated that lanthanide (Ln III )c omplexes can be used in solutiona ss ingle MLGMs, [9] sensors [10] and in parallel processes, [11] exploitingt heir characteristic emission properties.…”
mentioning
confidence: 94%
“…In the case of simple organic,o rc oordination compounds, [3] potential "outputs"c an be ac haracteristicc hange in both the absorption or the emission spectra of ac ompound. [4] These have been demonstrated elegantly by de Silva, [5] Andreasson, [6] and Pischel [7] amongsto thers. [8] Through our own work, we have demonstrated that lanthanide (Ln III )c omplexes can be used in solutiona ss ingle MLGMs, [9] sensors [10] and in parallel processes, [11] exploitingt heir characteristic emission properties.…”
mentioning
confidence: 94%
“…The phenanthroline moiety was incorporated into the molecule due to the known ability to coordinate with metal cations [22,23]. Dual-mode naked-eye molecular switches controlled by both light and changes in the ionic composition of the medium can be used as elements of electronic devices, for optical recording of information as well as in photopharmacology, light-gated catalysis and bioimaging [24][25][26]. In addition, such systems provide a conve-nient platform for creating chemo-and biosensors for rapid analysis of the ionic composition of the environment [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence switches are very useful notably for detection, imaging and optical storage devices. Therefore, they have applications in a large range of fields, from health to informatics via environment [2][3][4][5]. The concept of fluorescence switches requires a way to controllably and reversibly modify the luminescence intensity.…”
Section: Introductionmentioning
confidence: 99%